Enhancing Learning Outcomes in Salat Fardu Through the Demonstration Method and Drill Techniques - Sukarman, Sukarman; Latifah, Nurul (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2024)
This research aims to describe the application of demonstration methods and drill techniques on the subject of fardu prayers for grade 2 students at SD Negeri 3 Pelang , Mayong District, Jepara , and to describe learning outcomes on the subject of fardu prayers for grade 2 students at Pelang 3 Public Elementary School , Mayong Jepara . This research is classroom action research (CAR) with a qualitative approach. This research was conducted in class II of SD Negeri 3 Pelang . The research was conducted in the odd semester of 2023-2024. The primary data sources are PAI teachers, school principals, and grade 2 students at SD Negeri 3 Pelang . The data collection technique uses test, observation, interview, and documentation techniques. The data analysis techniques used are data reduction, data presentation, and conclusion. Data validity checking techniques use diligent observation, triangulation, and peer checking. The results of this research are: (1) The implementation of learning is divided into three cycles, namely Pre-Cycle, Cycle 1, and Cycle II. The use of demonstration methods and drill techniques on the subject of fardhu prayers by teachers in explaining, and demonstrating in front of the class and then students re-enacting the prayer movements and repeating them over and over helps learning. (2) Based on the results of the analysis carried out by researchers regarding learning outcomes from pre-cycle, cycle I, and cycle II, there has been an increase. In the pre-cycle, the average score was 58.75 with 16 students who completed and 16 who did not complete with a presentation of 50%. In cycle I the average score was 74.06 with 23 students who completed and 9 who did not complete with a presentation of 71.9%. Meanwhile, in cycle II the average score was 81.41 with 29 students who completed and 3 who did not complete with a presentation of 90.6%. With the increase in learning outcomes, many students have been able to perform and adapt the movements and read the fardu prayers correctly, although there are still some who have not yet mastered them completely.